COMPAÑÍA MINERA MALÚ S. A.” Un caso de evaluación de inversiones - Mendiola Cabrera, Alfredo (2002)
This study addresses the case of a mining company that needs to evaluate the feasibility of a new attractive prospect in the Callejón de Huaylas, department of Ancash, for having estimated gold reserves of 1.4 million ounces. Attending to this objective, it sets out in detail the set of variables to be considered for the evaluation: exploration period, detail engineering need, estimation of the ore grade and exploitation period, investment requirements, operation, and administration costs, financing needs, and taxes pressure. With these data and an intermediate assumption about the price of gold, it is established that the project would be viable with an investment of 40% of own resources and 60% of resources of third parties with an interest rate of 9%. A fall in the price of gold would force an increase in the proportion of own resources.